Employee Volunteering as Strategic Tool - Castañeda Abreu, Ana Amira (2015)
The current research explores how Spanish and British banks construct their employee volunteering practices and how they communicate them through their corporate reports, websites and employee volunteering portals by drawing on the framework of Kurucz et al. 2008 of competitive context. The aim of the research is to understand how firms leverage their capabilities and increase their competitive context by using their EVP as strategic tools. In the course of the study, a framework encapsulating the traits that an ideal type of strategic EVP should have is proposed to demonstrate how Strategic CSR might be achieved through Employee Volunteering. The findings indicate that contemporary Spanish and British banks have incorporated volunteer initiatives as a key element of their Corporate Responsibility strategy. The research illustrates how both countries have different strategies to enhance their competitive context and send a message to the firms’ stakeholders to express how they are truly committed to its social area. However, it also shows how they have not been able to discover the full value that Employee Volunteering has to offer.